400 - Environmental stimuli in nursing homes during the COVID-19 pandemic: Lessons learned to improve the management of challenging behavior. (October 2021) - Knippenberg, Inge; Leontjevas, Ruslan; Nijsten, Johanna; Bakker, Christian; Koopmans, Raymond; Gerritsen, Debby
Abstract : Challenging behavior is common in nursing home residents, especially in those with dementia. Our previous study suggested that a decrease in environmental stimuli (i.e., events that take place around residents but are not specifically directed at them) in nursing homes due to restrictions during the COVID-19 pandemic, may affect residents differently. To improve future care, the experience of practitioners can be used to learn about the effects of environmental stimuli on challenging behavior in specific resident groups during the pandemic. From the perspective of practitioners, this study aimed to learn from successful initiatives and observed effects of decreased environmental stimuli on challenging behavior in residents during anti-pandemic measures. An online survey among 199 Dutch nursing home practitioners was conducted from November 2020 to January 2021. Practitioners were asked about alleged effects of diminished environmental stimuli in residents with different types of challenging behavior (i.e., psychotic, depressed, anxious, agitated, apathetic) and with mild vs. advanced or without dementia. Also, their opinion about strategies to limit environmental stimuli was explored. Residents with advanced dementia and those with psychotic and agitated behavior seemed to benefit from diminished environmental stimuli. In contrast, residents without dementia and those with depressive and apathetic behavior seemed to be negatively affected by decreased environmental stimuli. Practitioners indicated that they would like to preserve various strategies to limit environmental stimuli in the future such as reducing the use of corridors adjacent to residents' rooms. Also, they planned to use adjustments and new initiatives regarding organized activities such as an increased use of small-scale and person-oriented activities. Opinions were divided on receiving visitors in the living room and on imposing visiting hours. In open-ended questions, other initiatives were mentioned that can be useful in nursing home care. Various strategies and initiatives in nursing homes during the pandemic seem promising to meet individual needs. While many residents may be negatively affected by restrictions during the pandemic, specific resident groups may benefit from a decrease in environmental stimuli. These findings underline the importance of a good balance between stimuli and rest in the nursing home, tailored to an individual resident.